Electromagnetic actuator design analysis using a two-stage optimization method with coarse-fine model output space mapping - Hey,J; Teo,TJ; Viet,PB; Yang,G; Martinez-Botas,R (IEEE Transactions on Industrial Electronics, 2014)
Electromagnetic actuators are energy conversion devices that suffer from inefficiencies. The conversion losses generate internal heat, which is undesirable, as it leads to thermal loading on the device. Temperature rise should be limited to enhance the reliability, minimize thermal disturbance, and improve the output performance of the device. This paper presents the application of an optimization method to determine the geometric configuration of a flexure-based linear electromagnetic actuator that maximizes output force per unit of heat generated. A two-stage optimization method is used to search for a global solution, followed by a feasible solution locally using a branch and bound method. The finite element magnetic (fine) model is replaced by an analytical (coarse) model during optimization using an output space mapping technique. An 80% reduction in computation time is achieved by the application of such an approximation technique. The measured output from the new prototype based on the optimal design shows a 45% increase in air gap magnetic flux density, a 40% increase in output force, and a 26% reduction in heat generation when compared with the initial design before application of the optimization method.